Development of site specific wind hazard map for peninsular Malaysia using geo-spatial modelling - Ramli, Noram Irwan (2019)
Hazard assessment is one of the coping capacity activity in minimise the effect of risk. In wind engineering the wind hazard assessment are evaluated based on the value of wind speed. Currently the value of wind speed is referred to basic wind speed (Vs). Basic wind speed is defined as the probability of the maximum wind speed within the return period. However, wind speed at specific location which is known as site wind speed (Vsite) should consider the effect of land use land cover and topography effect. Apart from that, wind hazard assessment on a spatial area is not feasible because of the Vsite value determined based on the point location. Therefore, the main objective of this study to develop the site specific wind hazard map by using geo-spatial technique. In MS 1553:2002 Vsite is calculated by multiplying the Vs with the Land Use Land Cover (LULC) factor denoted as Mz,cat, and topographic factor as Mh. In order to apply these formulae in a spatial area, Geographical Information System is used. This study also examined the wind hazard assessment by compare the performance of Vs map and Vsite map produced. For that reason, the past windstorm damage in Peninsular Malaysia is used to validate the performance of the wind hazard map produced. From the result, wind hazard map based on the site specific wind speed (Vsite) is highly recommended compared to the basic wind speed (Vs) map. The result showed that the damage occurred at lower Vs value compared to Vsite. Based on 50 years return period for windstorm damage cases, Vs is identified at 31.66 m/s which is 9.02% lesser when compared to value identified using Vsite which is equal to 34.80 m/s. It can be concluded that the risk assessment by referring only to Vs are misleading. Thus, the current risk assessment approach may underestimate the real potential of wind hazard for site specific location.